Odpowiedzi

Najlepsza Odpowiedź!
2010-03-08T17:03:48+01:00
A) x=-2, y=3
9y-(7y+x)+(6x-7y) = ??
9x3 –(7x3-2)+{6x(-2) -7x3}= 27–(21-2)+(-12-21)=
=27-21+2-12-21=-25
b) a=0,2, b=0,1
(6a-8b-0,7)-(6,9+a-5b)+1,8=
(6x2/10-8x1/10-7/10)-(69/10+2/10-5x1/10)+18/10=(12/10-8/10-7/10)-(69/10+2/10-5/10)+18/10=-3/10-66/10+18/10=-51/10
c) a=-2, b=1/2, c=-4
1/2abc-(4ab+2abc)+(-bc+5ab) =
=1/2x(-2)x1/2x(-4)-[4x(-2)x1/2+2x(-2)x1/2x(-4)]
+[-1/2x(-4)+5x(-2)x1/2]=2-(-8x1/2+8)+(2-5)=
2-(-4+8)+(-3)=2-4-3=-5
2010-03-08T17:09:42+01:00
A)9y-(7y+x)+(6x-7y)=9y-7y-x+6x-7y=-5y+5x=-5*(-2)+5*3=10+15=25
b)(6a-8b-0,7)-(6,9+a-5b)+1,8=6a-8b-0,7-6,9-a+5b=5a-3b-7,6=5*0,2-3*0,1-7,6=1-0,3-7,6=0,7-7,6=-6,9
c)1/2abc-(4ab+2abc)+(-bc+5ab)=1/2abc-4ab-2abc+(-bc)+5ab=ab-bc-1 1/2abc=-2*1/2-1/2*-4-1 1/2*(-2)* 1/2*(-4)=1+2+3-2=4

;) pozdrawiam ^^